Biotechnological potential of Synechocystis salina co-cultures with selected microalgae and cyanobacteria: Nutrients removal, biomass and lipid production - Ana L. Gonçalves (2016)
Cultivation of microalgae and cyanobacteria has been the focus of several research studies worldwide, due to the huge biotechnological potential of these photosynthetic microorganisms. However, production of these microorganisms is still not economically viable. One possible alternative to improve the economic feasibility of the process is the use of consortia between microalgae and/or cyanobacteria. In this study, Chlorella vulgaris, Pseudokirchneriella subcapitata and Microcystis aeruginosa were co-cultivated with Synechocystis salina to evaluate how dual-species cultures can influence biomass and lipid production and nutrients removal. Results have shown that the three studied consortia achieved higher biomass productivities than the individual cultures. Additionally, nitrogen and phosphorus consumption rates by the consortia provided final concentrations below the values established by European Union legislation for these nutrients. In the case of lipid productivities, higher values were determined when S. salina was co-cultivated with P. subcapitata and M. aeruginosa.